A survey on functional constipation and its risk factors in older people in Shahreza, Iran - Mina Amiri; Akbar Hassanzadeh; Majid Rahimi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Functional constipation is prevalent among older people. It has major effects on the quality of life of them, as well as the high costs of treatment. This study investigated functional constipation and risk factors affecting older people living in Shahreza, Iran. MATERIALS AND METHODS: This cross-sectional study was performed on 200 older people in Shahreza. They were selected by simple random sampling. We used the Rome III Criteria, the Elderly Physical Activity Questionnaire (PASE), and related questions from the SIB system (integrated health system). After completing the questionnaires, the data were analyzed using the mean and standard deviation, Chi-square test, independent-samples t-test, Fisher's exact test, and Mann-Whitney test. RESULTS: The prevalence of functional constipation was 45%. There are significant relationships between functional constipation with dental problems (P = 0.02), intake of fluid (P = 0.001), fruits (P = 0.001), and vegetables (P < 0.001), polypharmacy (P = 0.003), and antidepressants (P = 0.008), history of colon (P = 0.003) and anal (P = 0.001) diseases, stroke or mobility disabilities (P = 0.002), the level of physical activity (P = 0.002), and gender (P = 0.04) in older people living in Shahreza. CONCLUSIONS: According to the high prevalence of functional constipation in the studied older people, it is necessary to focus on controlling risk factors and planning to prevent the destructive effects of social restrictions on older people during the coronavirus disease 2019 (COVID-19) pandemic.